188k views
3 votes
Find the difference of (2n−9)−5(−2.4n+4)

1 Answer

3 votes

Answer: 2.071428571


Step-by-step explanation:Simplifying

(2n + -9) + -5(-2.4n + 4) = 0


Reorder the terms:

(-9 + 2n) + -5(-2.4n + 4) = 0


Remove parenthesis around (-9 + 2n)

-9 + 2n + -5(-2.4n + 4) = 0


Reorder the terms:

-9 + 2n + -5(4 + -2.4n) = 0

-9 + 2n + (4 * -5 + -2.4n * -5) = 0

-9 + 2n + (-20 + 12n) = 0


Reorder the terms:

-9 + -20 + 2n + 12n = 0


Combine like terms: -9 + -20 = -29

-29 + 2n + 12n = 0


Combine like terms: 2n + 12n = 14n

-29 + 14n = 0


Solving

-29 + 14n = 0


Solving for variable 'n'.


Move all terms containing n to the left, all other terms to the right.


Add '29' to each side of the equation.

-29 + 29 + 14n = 0 + 29


Combine like terms: -29 + 29 = 0

0 + 14n = 0 + 29

14n = 0 + 29


Combine like terms: 0 + 29 = 29

14n = 29


Divide each side by '14'.

n = 2.071428571


Simplifying

n = 2.071428571


User Willona
by
4.9k points